Relationship between salivary stress biomarker levels and cigarette smoking in healthy young adults: an exploratory analysis - Suzuki, Nao (Tob Induc Dis, 2016)
BACKGROUND: This study investigated the relationships among salivary stress biomarkers, cigarette smoking, and mood states. METHODS: The study population comprised 49 healthy sixth-year dental students at Fukuoka Dental College (39 men, 10 women; age, 23–31 years). Lifetime exposure to smoking was calculated using the Brinkman index (BI). Resting saliva samples were collected, and concentrations of cortisol, secretory immunoglobulin A (SIgA), interleukin (IL)-1β, interleukin-6, and tumor necrosis factor (TNF)-α were determined. Mood states (tension-anxiety, depression-dejection, anger-hostility, fatigue, confusion, and vigor) over the previous week were assessed using the Profile of Mood States - Brief Japanese Version. RESULTS: Salivary IL-1β levels were significantly higher in smokers than non-smokers (P = 0.044), regardless of the BI or mood state. A significant positive correlation was evident between the TNF-α level and the BI (P = 0.036), and the SIgA level was positively correlated with the BI (P = 0.067) but did not reach statistical significance. In terms of mood states, higher fatigue scores and lower vigor scores were observed in smokers. The TNF-α level and vigor score were negatively correlated (r = –0.229, P = 0.135), but the correlation did not reach statistical significance. However, the SIgA level and fatigue score were significantly positively correlated (r = 0.410, P = 0.005). CONCLUSIONS: The TNF-α and SIgA levels were both positively correlated with the BI. Furthermore, the TNF-α level was negatively correlated with the vigor score, whereas the SIgA level was positively correlated with the fatigue score. Thus, salivary levels of TNF-α and SIgA may be used as biomarkers of mood states in healthy young smokers.